Sistem Informasi Penjualan Furniture Berbasis Web Menggunakan Bahasa Pemrograman Php Mysql - putri, Perra Budiarti Rahayu; Wijaya, Anggi Hadi (Jurnal Sains dan Teknologi (JSIT), 2021)
This research was conducted at the Berkat Furniture Store, this study aims to create a Web-based furniture sales information system at the Berkat Furniture Store.With this system, it is hoped that it can provide convenience in the process of promoting products to the process of selling furniture, starting from ordering and making it easier for consumers to make transactions online and anywhere without consumers having to come to the store to get a product they want. And in designing the application, the PHP programming language and MySQL database are used which aims to make it easier for users to understand and understand.